2014
DOI: 10.1186/s13012-014-0118-8
|View full text |Cite
|
Sign up to set email alerts
|

Instrumentation issues in implementation science

Abstract: BackgroundLike many new fields, implementation science has become vulnerable to instrumentation issues that potentially threaten the strength of the developing knowledge base. For instance, many implementation studies report findings based on instruments that do not have established psychometric properties. This article aims to review six pressing instrumentation issues, discuss the impact of these issues on the field, and provide practical recommendations.DiscussionThis debate centers on the impact of the fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
195
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(200 citation statements)
references
References 56 publications
1
195
0
4
Order By: Relevance
“…Similar to other areas of implementation research, this endeavor presents methodological challenges, many of which hinge on the valid and reliable assessment of sustainability predictors, the outcomes, and the sustainment strategies being implemented (25, 83,106). There is emerging evidence for the reliability and validity of a small number of sustainability-specific assessments and tools, which are designed to determine an organization's capacity in key factors (e.g., partnerships, strategic planning) that have been shown to be linked to sustainment success (61,76) and to develop a strategic action plan for building capacity in areas of weakness (19,35,65,113).…”
Section: Planning For and Strategies To Enhance Sustainabilitymentioning
confidence: 99%
“…Similar to other areas of implementation research, this endeavor presents methodological challenges, many of which hinge on the valid and reliable assessment of sustainability predictors, the outcomes, and the sustainment strategies being implemented (25, 83,106). There is emerging evidence for the reliability and validity of a small number of sustainability-specific assessments and tools, which are designed to determine an organization's capacity in key factors (e.g., partnerships, strategic planning) that have been shown to be linked to sustainment success (61,76) and to develop a strategic action plan for building capacity in areas of weakness (19,35,65,113).…”
Section: Planning For and Strategies To Enhance Sustainabilitymentioning
confidence: 99%
“…165 Finally, a comprehensive review of 6 key instrumentation issues that have emerged in implementation science has been undertaken. 99 These include the explicit use of frameworks, theories and models; specific psychometric evaluation of tests; choice of appropriate tests; choice of most appropriate methods of evaluation; practical utility; and the need for decision making tools. A number of practical recommendations in terms of consensus definitions, reporting standards, and methods also are suggested.…”
Section: New Approaches To Pain Instrument Developmentmentioning
confidence: 99%
“…New tools for pain assessment include visual computerizedassisted representation, 98 a data-driven multidimensional scaling method using a neural network, 120 a tool designed to enhance physician-patient communication, 99 web-based tools 87 and a method for thematic analysis of pain-related mental imagery. 52 These tools are described in Table S6 (available online as Supplemental Digital Content at http:// links.lww.com/PAIN/A201).…”
Section: New Pain Assessment Toolsmentioning
confidence: 99%
“…However the latter training also involved extensive expert consultation and session review of a kind that is not scalable; thus the findings are not directly comparable. Although positive changes in knowledge and skill have been reported for web based training, studies have employed widely varying methods and few have employed standardised outcome measures making it difficult to draw firm conclusions [11,12]. One study of web based training in transdiagnostic cognitive behaviour therapy for community clinicians that used an established measure, reported that 48% reached competency but the training also included 7.5 months of face-to face consultation with previously trained peers and 6.5 hours of expert instructor time [29].…”
Section: Comparisons With Other Studiesmentioning
confidence: 99%